The Engro Zarkhez Challenge 2011. (March 2013) - Alvi, Sara; Butt, Arif N.; Khurshid, Anwar; Siddiqui, M. Athar
The case aims at highlighting the intra organizational negotiation challenges faced by Engro Marketing team for attaining sales targets. The problem is of goal incongruence and lack of communication regarding sales targets in the organization. Additionally, the structural changes which had added a new layer of management of Area Marketing Managers (AMMs) in Engro led to role ambiguities between the Area Marketing Managers (AMM) and the Zonal Marketing Managers (ZMM). The main challenges that Engro faces are: a) There was an urgent need for differing viewpoints on sales targets to converge to a joint goal setting pattern b) Up-gradation of skills was needed by AMM and ZMM with respect to increased listening and communication, facing and appreciating work-related conflict, working out interpersonal frictions and not using compromise as a basis for organizational decision-making, and c) A commitment to the strategic goals of the company needed to be gained by establishing clear responsibilities for implementing them.